Korelasi Aktivitas Fisik dengan Subjective Well-Being pada Mahasiswa Sarjana Pendidikan Dokter dalam Menghadapi Pembelajaran Tatap Muka di Bandar Lampung - Kasyfi, Fathul Qadir; Putri, Asri Mutiara; Widodo, Slamet; Pramesti, Woro (Universitas Malahayati, 2023)
ABSTRACT Individuals who experience mental disorders have a poor impact on physical activity or are reluctant to do so, the individual is not subjective well-being and vice versa. Almost all medical students experience psychological problems, due to their busy learning activities and many learning activities. Subjective well-being in students is influenced by several factors, namely demographics, social support, stress levels, social activities, healthy lifestyles and the environment. Medical students enjoy doing physical activities that have a positive impact on their mental health. In addition, it provides an overview of mental health or subjective well-being in students when returning to face-to-face learning and knowing the factors that need to be improved to help students achieve good mental health or subjective well-being. To determine the correlation of physical activity with subjective well-being in undergraduate medical education students in facing face-to-face learning. This study was a quantitative research with analytic survey design and cross-sectional design. The research sample amounted to 139 medical students in Bandar Lampung. The measuring instruments used were student demographic data and Positive Affect Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS) and Health Promoting Lifestyle Profile II (HPLP II). Most respondents had moderate physical activity levels (96.4%) and negative subjective well-being (38.1%). The correlation analysis results obtained a p-value of 0.000. There is a correlation between physical activity and subjective well-being in undergraduate medical education students in facing face-to-face learning in Bandar Lampung. Keyword : Physical Activity, Subjective Well-Being, Medical Students, Learning, Face-to-Face ABSTRAK individu yang mengalami gangguan mental berdampak buruk dalam melakukan aktivitas fisik atau enggan melakukannya, individu tersebut tidak subjective well-being begitu juga sebaliknya. Hampir semua mahasiswa kedokteran mengalami masalah psikologis, dikarenakan aktivitas belajarnya padat dan banyak kegiatan pembelajaran. Subjective well-being pada mahasiswa dipengaruhi oleh beberapa faktor, yaitu demografi, dukungan sosial, tingkat stres, aktivitas sosial, gaya hidup sehat dan lingkungan. Mahasiswa kedokteran senang dalam melakukan aktivitas fisik berdampak positif pada kesehatan mentalnya. Selain itu, memberikan gambaran kesehatan mental atau subjective well-being pada mahasiswa saat kembali belajar tatap muka dan mengetahui faktor yang perlu ditingkatkan untuk membantu mahasiswa mencapai kesehatan mental atau subjective well-being yang baik. Untuk mengetahui korelasi aktivitas fisik dengan subjective well-being pada mahasiswa sarjana pendidikan dokter dalam menghadapi pembelajaran tatap muka. Jenis penelitian kuantitatif dengan desain survei analitik dan rancangan cross-sectional. Sampel penelitian berjumlah 139 mahasiswa kedokteran di Bandar Lampung. Alat ukur yang digunakan adalah data demografi mahasiswa dan Positive Affect Negative Affect Schedule (PANAS), Satisfaction With Life Scale (SWLS) dan Health Promoting Lifestyle Profile II (HPLP II). Sebagian besar responden memiliki tingkat aktivitas fisik sedang (96,4%) dan subjective well-being negatif (38,1%). Hasil analisis korelasi didapatkan p-value 0,000. Terdapat korelasi aktivitas fisik dengan subjective well-being pada mahasiswa sarjana pendidikan dokter dalam menghadapi pembelajaran tatap muka di Bandar Lampung. Kata Kunci : Aktivitas Fisik, Subjective Well-Being, Mahasiswa Kedokteran, Pembelajaran, Tatap Muka